Fashion design education students' ability to create fashion patterns: investigating the effect of antecedent factors - Ernawati Ernawati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This study is based on the problem of many students having a low ability to create fashion patterns. This study aimed at the influence of knowledge, discipline, and facility on the fashion design education students' ability to create fashion patterns. The total population was 65 students that enrolled in the Fashion Pattern Construction of the Fashion Design Education Program of Universitas Negeri Padang. The sampling technique used in this study is total sampling. A total of 65 respondents were successfully collected. The data analysis technique used is Partial Least Square Structural Equation Modelling (PLS-SEM). The results showed that: There is an insignificant influence of knowledge on fashion design education students’ ability to create fashion patterns. Meanwhile, there is a significant effect of discipline and facility on fashion design education students’ ability to create fashion patterns. What could be said from the result of the study is that high discipline of students in the learning process and adequate facilities are owned by students and provided by the university could be increased fashion design education students' ability to create fashion patterns.